Expression patterns of serum MicroRNAs related to endothelial dysfunction in patients with subclinical hypothyroidism - Yao, Xuelin; Wang, Ying; Wang, Li; Cao, Mingfeng; Chen, Aifang; Zhang, Xinhuan (Frontiers in Endocrinology, 2022)
Background: Increasing evidence has shown that elevated Thyroid stimulating hormone (TSH) levels are positively correlated with atherosclerosis (ATH) in patients with subclinical hypothyroidism (SCH). Some researchers found that the dysfunction of Endothelial Cells (ECs) in SCH plays an important role in the pathogenesis of ATH in SCH, but the association remains controversial. Objectives: To determine the expression profiles of serum microRNAs critical to the function of Endothelial cells (ECs) may help reanalyse the possible mechanism underlying ATH in SCH and the association between ATH and SCH. Methods: We used qRT-PCR to perform microRNA profiling and analysis in normal control subjects (NC), patients with SCH alone (SCH), patients with SCH and ATH (SCH+ATH), and patients with ATH without SCH (ATH). Results: Both miR-221-3p and miR-222-3p showed a decreasing expression trend between the SCH and SCH+ATH groups. In addition, miR-126-3p and miR-150-5p showed a stepwise decrease from the NC to SCH groups and then to the SCH+ATH or ATH group. miR-21-5p was unregulated in the SCH, SCH+ATH, and ATH groups. Furthermore, elevated levels of miR-21-5p in SCH+ATH group were higher than SCH and ATH group. No differneces were found in the levels of miR-150, miR-126, miR-221 and miR-222 between the ATH and the SCH+ATH subjects. Conclusions: miR-21-5p may be involved in the atherosclerosis process in patients with SCH (SCH and SCH+ATH groups). miR-150-5p may be sensitive risk markers for predicting endothelial dysfunction in patients with ATH (ATH and SCH+ATH groups).